Constructing a Development Methodology for Web-based Information Systems with Information Quality - Abdul-Aziz, Azlianor; Koronios, Andy; Gao, Jing; Sulong, Muhammad Suhaizan (2012)
In recent years, with the rapid evolution of web technologies, the complexity of web-based information systems has grown significantly. Without a proper web development methodology, it would be difficult to assist the web development team during the web development process. Even where there is a specifically designed methodology for web development, if information quality is not considered especially by the web development team, the entire web development would fail. The level of information quality for the task in hand is therefore important. This paper aims to identify the need for an information quality framework for the web development methodology in order to discover information quality issues, with associated information quality requirements, at each stage of web development methodology and to construct a specific information quality framework. The framework is envisaged to perform as a pre-reference guide for the web development team for effective development of web-based information systems.